Serum vascular endothelial growth factor (vegf) as a biomarker of lupus nephritis - Iberahim, Rahimah (2013)
Systemic lupus erythematosus (SLE) is a multisystem autoimmune disorder with a broad spectrum of clinical presentations (Tan EM et al, 1982). SLE is a chronic illness that may be life-threatening when major organs are affected but more commonly results in chronic debilitating ill health. It is characterised by pathogenic auto antibodies production and tissue deposition of immune complexes. No single cause for SLE has been identified though factors such as sunlight and drugs may precipitate the condition and there is a complex genetic basis. The incidence of SLE in the general population varies according to the characteristics of the population studied, i.e. age, gender, race, ethnic/national origin or period of time studied, but also depending on changes in classification criteria. SLE is more common among women in their reproductive years (Cross and Benton, 1999), with highest incidence seen in premenopausal period between the ages of 20 to 50 years (Siegle et al, 1970; Hochberg, 1985) and female to male ratio range from 6 to 14:1 (McCarty et al, 1995; Voulgari et al, 2002; Soto ME et al, 2004). The prevalence of SLE in United States is 1 in 250 in black females and 1 in 1000 in white females (Manolios and Schrieber, 1997). Estimated incidence rates in North America, South America and Europe range from 2 to 8 per 100 000 per year (Vilar and Sato, 2002; Jeminez et al, 2003), tripling in the last 40 years due to improved detection of mild disease. Both geography and race effect affect SLE prevalence. SLE is more common in the urban than rural areas; and there is higher prevalence among Asians, Afro- American, Afro-Carribbeans, Hipanic Americans (Serdula and Rhoads, 1979; Hochberg, 1985; Lawrence et al, 1989) but lower prevalence among blacks in Africa (Symmons, 1995). A study by Hopskinson et al (1994) revealed that the highest prevalence rate was seen in Afro- Carribbeans (207/100 000), followed by Asians (48.8/100 000). Racial differences in the clinical features of SLE have also been noted, with blacks developing SLE at younger age, discoid lupus being more common, and higher prevalence of antibodies to Smith (Sm) and Ribonucleoprotein (RNP) antigen, compared to whites (Ward and Studenski, 1990). Previous study in Malaysia reported a ratio of 12:1 was seen in all major ethnic group; Malays, Chinese and Indian (Wang et al, 1997). A person is having SLE if she or he fulfils 4 out of 11 criteria based on 1997 American Rheumatism Association (ARA) revised criteria, which confers 96% sensitivity and specificity (Hochberg, 1997). The eleven criteria are described in Table 1.1.